High efficiency Raman memory by suppressing radiation trapping - Thomas, S; Munns, J; Kaczmarek, K; Qiu, C; Brecht, B; Feizpour, A; Ledingham, P; Walmsley, I; Nunn, J; Saunders, D (IOP Publishing, 2017)
Raman interactions in alkali vapours are used in applications such as atomic clocks, optical signal processing, generation of squeezed light and Raman quantum memories for temporal multiplexing. To achieve a strong interaction the alkali ensemble needs both a large optical depth and a high level of spin-polarisation.Weimplement a technique known as quenching using a molecular buffer gas which allows near-perfect spin-polarisation of over 99.5% in caesium vapour at high optical depths of up to ∼2 × 10 5 ; a factor of 4 higher than can be achievedwithout quenching.We use this systemto explore efficient light storage with high gain in a GHz bandwidth Raman memory.